Safety assessment of commensal enterococci from dogs - Kubašová, Ivana; Strompfová, Viola; Lauková, Andrea (Folia microbiologica, 2017)
Enterococci form a complex, diverse, and very important group of bacteria from the technological and food safety aspect, or from the health-improving aspect as probiotics. Generally, enterococci are considered to be of low pathogenic potential, which is associated mostly with clinical strains. In these strains, production of virulence factors as well as resistance to many antimicrobial drugs could complicate treatment of nosocomial infections. Because there is a lack of information on incidence of these attributes in animal commensal enterococci, we screened 160 strains originating from feces of clinically healthy dogs in Eastern Slovakia (n = 105). The predominant species were Enterococcus faecium (57.5%) followed by Enterococcus faecalis (21.9%), and Enterococcus hirae (17.5%), while Enterococcus casseliflavus (1.9%) and Enterococcus mundtii (1.2%) rarely occurred. Among the tested antibiotics, gentamicin (high level) was the most effective drug against canine enterococci (95% of isolates were sensitive). In contrast, the highest resistance recorded (71.9%) was to teicoplanin. PCR screening showed the highest incidence of virulence genes in E. faecalis species. The most frequently detected were genes encoding adhesins efa Afm and efa Afs and sex pheromone cpd. IS16 gene, a marker specific for hospital strains, appeared in nine E. faecium strains. No strain was positive for DNase activity, 8.8% of the isolated strains showed gelatinase activity, and almost 100% strains produced tyramine. It seems commensal-derived enterococci from dogs could also to some extent be potential reservoir of risk factors for other microbiota or organisms.
Keywords: antibakteriální látky; Microbial Sensitivity Tests; Virulence Factors; Enterococcus; Anti-Bacterial Agents; Dogs; Animals; Symbiosis; mikrobiální testy citlivosti; Bacterial Proteins; symbióza; Drug Resistance, Bacterial; faktory virulence; zvířata; psi; bakteriální proteiny; bakteriální léková rezistence